Acceleration of kidney function decline after incident hospitalization with cardiovascular disease: the Stockholm CREAtinine Measurements (SCREAM) project. (20th August 2020) - Ishigami, Junichi; Trevisan, Marco; Lund, Lars H.; Jernberg, Tomas; Coresh, Josef; Matsushita, Kunihiro; Carrero, Juan‐Jesus
Abstract : Aims: The cardiorenal syndrome refers to a bidirectional relationship between the kidney and the heart. However, epidemiological evidence of cardiovascular disease (CVD) as a risk factor for chronic kidney disease (CKD) progression is actually scarce. Methods and results: We examined the slopes of estimated glomerular filtration rate (eGFR) decline in the 2 years before vs. after an incident hospitalization with heart failure (HF) ( n = 20 420), coronary heart disease (CHD) ( n = 18 152), or stroke ( n = 1808) using data from a complete laboratory data collection in Stockholm, Sweden between 2006 and 2011. eGFR slopes were estimated using mixed‐effect models with unstructured residual correlation. Overall, incident hospitalization with HF and CHD, but not stroke, was significantly associated with a subsequent accelerated decline in eGFR, with a faster eGFR decline and greater slope change after HF than CHD. The pre‐event vs. post‐event eGFR slopes (mL/min/1.73 m 2 per year) were −1.67 (−1.77 to −1.57) vs. −2.76 (−2.82 to −2.71), with a Δslope of −1.09 (−1.16 to −1.02) for HF; −1.09 (−1.20 to −0.98) vs. −1.87 (−1.92 to −1.81), with a Δslope of −0.78 (−0.85 to −0.70) for CHD; and −1.00 (−1.37 to −0.63) vs. −0.99 (−1.19 to −0.78), with a Δslope of 0.02 (−0.24 to 0.27) for stroke. The accelerated declines in eGFR after HF and CHD were consistent across the spectrum of eGFR, although pre‐event eGFR slopes were steeper in lower eGFR (e.g. pre‐event eGFR slope for HF −0.64 (−0.76 to −0.53) for eGFR ≥60 mL/min/1.73 m 2, −1.43 (−1.57 to −1.30) for eGFR 30–59 mL/min/1.73 m 2, and −2.42 (−2.71 to −2.12) for eGFR <30 mL/min/1.73 m 2 ). Conclusions: Incident hospitalization with cardiac diseases (i.e. HF and CHD) was significantly associated with a subsequent acceleration of eGFR decline.